Scoring Systems for Diagnosis of Acute Venous Thromboembolism - Le Gal, Grégoire; Righini, Marc; Wells, Philip S. (Seminars in Thrombosis and Hemostasis, 2017)
Modern diagnostic strategies for venous thromboembolism almost all rely on an initial assessment of the pretest probability. Assessing the patient's pretest probability for venous thromboembolism is a critical step in the diagnostic strategy and for therapeutic management. Clinical prediction rules combine medical signs and symptoms to provide accurate and reproducible estimates of the probability of a disease before diagnostic tests are performed. The use of scoring systems in patients with suspected acute venous thromboembolism should be encouraged, as their implementation in guidelines for venous thromboembolism diagnosis results in cost-effective care with improved patient outcomes.
Keywords: clinical probability; clinical prediction rules; pulmonary embolism; deep vein thrombosis; diagnostic algorithm